Juventude e educação não formal: as rodas e outras vivências na associação de capoeira arte e recreação berimbau de ouro, na cidade de Santo Amaro - Ba - Dos Santos, Maura Evangelista (2016)
This paper focus on educational processes developed through the relation among youth, non-formal education and capoeira, one of the most important cultural expressions of African roots in Brazil. The main objective is to understand the socio-educational and cultural implications of the experiences of the young people attending the “Associação de Capoeira Arte e Recreação Berimbau de Ouro – ACARBO”, from Santo Amaro da Purificação, Bahia. We seek the significance and meanings of these experiences in the perception of those involved, in a territory marked by socioeconomic vulnerability and by a historical and affective memory permeated by different forms of belonging, identities and sociabilities. The research situated on popular culture and African worldview is ethnographic, which includes participant observation and open interviews with three young men and a Master of Capoeira. In the theoretical and methodological level, for the investigated scenario, we establish a dialogue with, among others, the following authors: ABIB (2005), BARROS (2009), DAYRELL (1996; 2007); MACEDO (2004), PETIT, (2015), SILVA E PETIT (2011; 2013), GOHN (2006; 2010); PAIS (1996; 2003); PARK (2005). As of a result of this research, I found that the experiences of young people within the association, in intergenerational living associated with popular culture and African worldview, transpose both the limits of formal education, which is not always welcomed in daily life and curriculum knowledge originating in African -Brazilian culture, as the very mass culture conveyed in the hegemonic media means. The practice of capoeira combined with other educational dynamics, like the group conversations, workshops, training classes, theater, etc. in that association , for its educational influence, contributes to the participant’s civic education, revealing social and cultural emancipation possibilities. In addition, the educational practices mediated by body art can represent an appropriation of the ethnic group culture, bringing new meanings and resistance devices and coping with situations of social exclusion.